EMI OR BILINGUAL INSTRUCTION? AN EXPERIMENTAL STUDY IN THE TEACHING OF ORAL COMMUNICATION AMONG PHILIPPINE SENIOR HIGH SCHOOL STUDENTS - Minoza, Joemar; Albiso, Maria Concepcion; Armas, Ayessa Keith; Calisang, Angelica (Kantor Jurnal dan Publikasi Universitas Pendidikan Indonesia, 2024)
Bilingual instruction has gained its popularity and importance as an alternative instructional strategy of English as medium of instruction in a classroom setting. Bilingual instruction is oftentimes associated with the use of code-switching, which is still presumed as an asset during the giving of the lessons which includes teaching and learning interaction between the learners and the teacher. This study examines the use of code-switching and measures the effectiveness of bilingual instruction by looking into the mean gain of the pre-and post-test scores of the control (EMI) and experimental (Bilingual Instruction) groups employing a quasi-experimental method. Senior high school students who are non-native speakers of English were involved in this study. Two classes who were under different teaching modalities with regards to the aligned competency used during the conduct of the study; had undergone observation, and audio recording, which was transcribed to analyze why and how bilingual instruction was used. The analysis of bilingual instruction revealed that both bilingual instruction and EMI are effective tools in improving the language proficiency of the teacher and understanding of the subject Oral Communication as manifested in the mean gain. Therefore, whatever medium is used, they could be effective as long as the teacher knows what he is teaching and applies appropriate strategies in the teaching and learning process. This calls for the school administrators to encourage the use of bilingual instruction since there are students that are still left behind when it comes to communicative competence and have lower cognitive skills when English is used as medium of instruction.